Fast mirrors for femtosecond passive mode-locked near-infrared lasers. (27th October 2016) - Rubtsova, N N; Borisov, G M; Ledovskikh, D V; Kovalyov, A A; Preobrazhenskii, V V; Putyato, M A; Semyagin, B R; Kisel', V E; Rudenkov, A S; Kuleshov, N V; Pavlyuk, A A
Abstract: The design, manufacturing and characterization of the near infrared fast, low non-saturable loss semiconductor mirrors with saturable absorption based on InGaAs quantum wells separated by super-lattice GaAs/InGaAs barriers are analyzed from the viewpoints of recovery time shortening mechanism and of further improvement of mirror performance.